Efektivitas dan Tantangan Penggunaan Media Pembelajaran Interaktif di Sekolah Dasar - Salsabila Dwi Karna; Adrias Adrias; Aissy Putri Zulkarnaini (Pusat Riset dan Inovasi Nasional, 2025)
Technological advances have encouraged innovation in education, including the use of interactive learning media in primary schools aims to enhance student engagement and improve learning outcomes. This study analyzes the impact, challenges, and effectiveness of interactive media through a literature review of relevant scientific journals. The findings reveal that tools such as PowerPoint, educational videos, and Kahoot significantly boost student motivation, facilitate better understanding of concepts, and promote active participation. However, challenges like limited access to technology, teacher preparedness, and varying student competencies must be addressed to maximize the potential of these media in education, among other things, increase interest in learning, facilitate understanding of the material, and encourage active participation of students. They also support independent learning, help students and teachers develop technology skills, and improve information retention, thus creating a more effective, efficient and enjoyable learning experience. However, challenges such as limited access to technology and teachers' lack of skills in operating interactive media are still an obstacle. With good planning and training for educators, interactive learning media can be an innovative solution in creating a more effective, fun and meaningful learning process for students in the digital era